High Serum Levels of Otolin-1 in Patients With Benign Paroxysmal Positional Vertigo Predict Recurrence - Fan, Zhenyi; Hu, Zhizhou; Han, Weiwei; Lu, Xiaoxiong; Liu, Xiaoxia; Zhou, Min; Yan, Wang; Wu, Yunqin (Frontiers in Neurology, 2022)
Background: Otolin-1 is an inner ear-specific protein that is exclusively expressed in otoconia and vestibule and cochlea cells. Recent investigations reported that otolin-1 can cross the blood-labyrinthine barrier and be measured and that the levels in serum well reflected otolith status. Serum otolin-1 levels in patients with benign paroxysmal positional vertigo (BPPV) are significantly elevated compared with healthy controls. We aimed to explore whether otolin-1 can also serve as a biomarker for predicting BPPV recurrence. Method: New-onset patients with idiopathic BPPV at our institution from May 2017 to May 2018 were recruited and followed up 2 years. All patients’ demographic data were collected, and serum levels of otolin-1 and other laboratory indicators were measured and compared according to the recurrence status. Results: A total of 74 patients meeting the inclusion criteria were enrolled in this study, and 27 (36.5%) patients had suffered one or more episodes of recurrence after undergoing canal repositioning treatments during the study. The serum levels of otolin-1 in patients with recurrent BPPV were significantly higher than those in patients without recurrent (363.9 pg/ml vs. 309.8 pg/ml, P = 0.001).In multivariate analysis comparing the second to fourth quartiles (Q2-Q4) against the first quartile (Q1) of otolin-1, the level of otolin-1 in Q4 could significantly predict BPPV recurrence, and the odds ratio was elevated by approximately 812% (OR = 9.12; 95% CI: 1.44–57.9; P=0.019). Conclusion: High serum levels of otolin-1 were associated with an increased risk of BPPV recurrence, and further investigation is required to confirm this association and clarify the exact mechanism.